Peran Kepala Sekolah dalam Membangun Karakter Disiplin Siswa SD Negeri 51/1 Simpang Kubu Kandang - Anggun Revina Sirait; Tabroni Tabroni (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study discusses the role of the school principal in building the discipline character of students at SD Negeri 51/1 Simpang Kubu Kandang. The issue at hand is the low level of discipline and the underdeveloped character of the students, which hinders the teaching and learning process. This study aims to analyze the principal's role, the challenges faced, and the efforts made in shaping the students' discipline character. The research method used is qualitative with a case study approach, and data analysis techniques include reduction, presentation, and verification. The findings show that the principal plays a role as a leader who provides direction, a supervisor who monitors the implementation of policies, and a motivator who encourages students to improve their discipline. The challenges faced include the lack of control over students' discipline outside the school and the low awareness of students in applying disciplined behavior. The solutions implemented by the principal include providing role models, guidance, reprimands, and carrying out habituation activities to instill discipline. This study provides an overview of the important role of the school principal in creating a discipline culture that supports the teaching and learning process.